2009
DOI: 10.1007/s10620-009-0977-z
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines and Cytokines in Human Pancreatic Juice: Unraveling the Local Pancreatic Inflammatory Milieu

Abstract: This report is the first to describe adipokine expression in human pancreatic juice. Human pancreatic juice inflammatory mediators and adipokines may provide an important measurement of the local pancreatic inflammatory milieu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…One prospective study reported that the median plasma adiponectin concentration is lower in case subjects compared with control subjects [11]. In contrast, many other studies found higher serum adiponectin levels or a higher adiponectin/leptin ratio in pancreatic cancer patients who exhibited a positive or strong positive expression of AdipoR1 and AdipoR2 and that this higher level correlated strongly with the proinflammatory cytokine IL-6 [2, 12-14]. Importantly, adiponectin can protect against pancreatic beta cell apoptosis by the induction of Erk and Akt phosphorylation [15].…”
Section: Introductionmentioning
confidence: 99%
“…One prospective study reported that the median plasma adiponectin concentration is lower in case subjects compared with control subjects [11]. In contrast, many other studies found higher serum adiponectin levels or a higher adiponectin/leptin ratio in pancreatic cancer patients who exhibited a positive or strong positive expression of AdipoR1 and AdipoR2 and that this higher level correlated strongly with the proinflammatory cytokine IL-6 [2, 12-14]. Importantly, adiponectin can protect against pancreatic beta cell apoptosis by the induction of Erk and Akt phosphorylation [15].…”
Section: Introductionmentioning
confidence: 99%